A comunicação do amor romântico no pop-rock brasileiro: um estudo do imaginário nos processos criativos de Erasmo Carlos, Rita Lee, Lobão e Pato Fu - Anaz, Sílvio Antonio Luiz (2013)
Romantic love is one of the most habitual subjects in the international pop-rock songs since the 1950 s. It is a regular topic in the Brazilian pop-rock songs in the same period, too. Those Brazilian and international pop-rock songs have built a romantic love imaginary that has been disseminated by the cultural industry and mass communication media. In this research, we look for understanding the processes that have participated in the building of the Brazilian pop-rock songs imaginary, based on their lyrics and music, and in the histories, tastes, world visions and networks of a group of Brazilians composers that are representatives of this kind of song. This research looks for understanding through the imaginary the cultural identification process established among the composers and the audience of these songs. The mapping of romantic love imaginaries and the investigation of their construction processes can be revealing of a individual feeling of sharing and belongingness to specific imaginaries in the songs universe. The hypothesis is that the Brazilian pop-rock imaginary is produced by world visions convergence and by seduction, cultural identification and adhesion of composers and audiences to a specific musical ethos, that transcend boarders and result in an aesthetic, ethic and behavior approximation between Brazilian and international pop-rock songs. The investigation maps the romantic love imaginaries in the international pop-rock hits, in the second half of 20th century, and that built in the Erasmo Carlos, Rita Lee, Lobão and Pato Fu songs, Brazilian composers representatives of these musical genres in the same period. The investigation looks for identifying, using a semantic romantic love mapping, what are the main symbolical elements in these imaginaries that came from the creative processes of Brazilian composers, and became references of the approaching between Brazilian and international pop-rock songs. The theoretical reference in this research brings authors in the imaginary field, such as Gilbert Durand and Michel Maffesoli, semiotics, such as Charles Sanders Peirce, Roland Barthes and Umberto Eco, and culture and communications, such as Jesus Martín-Barbero and Stuart Hall. The conclusion shows how songs and creative processes of Brazilian composers built a romantic love imaginary that could be a expression of the feeling of belongingness and cultural identification process, that brings closer local and global aesthetics, ethics and behaviors established by successful songs